Changes in Primary Non-Cardiac Diagnoses over Time Among Elderly Cardiac Intensive Care Unit Patients in the United States - Sinha, Shashank S. (Circ Cardiovasc Qual Outcomes, 2017)
BACKGROUND: Early reports suggest the number of CICU patients with primary non-cardiac diagnoses is rising in the U.S., but no national data currently exist. We examined changes in primary non-cardiac diagnoses among elderly patients admitted to a cardiac intensive care unit (CICU) over the last decade. METHODS AND RESULTS: Using 2003–2013 Medicare data, we grouped elderly patients admitted to CICUs into two categories based on principal diagnosis at discharge: 1) primary non-cardiac diagnoses and 2) primary cardiac diagnoses. We examined changes in patient demographics, comorbidities, procedure use, and risk-adjusted in-hospital mortality. Among 3.4 million admissions with a CICU stay, primary non-cardiac diagnoses rose in prevalence from 38.0% to 51.7% between 2003 and 2013. The fastest rising primary non-cardiac diagnoses were infectious diseases (7.8% to 15.1%) and respiratory diseases (6.0% to 7.6%) (p < 0.001 for both), while the fastest declining primary cardiac diagnosis was coronary artery disease (32.3% to 19.0%) (p < 0.001). Simultaneously, the prevalence of both cardiovascular and non-cardiovascular comorbidities rose: heart failure (13.9% to 34.4%), pulmonary vascular disease (1.2% to 7.1%), valvular heart disease (5.0% to 9.8%) and renal failure (7.1% to 19.6%) (p < 0.001 for all). As compared with those with primary cardiac diagnoses, elderly CICU patients with primary non-cardiac diagnoses had higher rates of non-cardiac procedure use and risk-adjusted in-hospital mortality (p < 0.001 for all). Risk-adjusted in-hospital mortality declined slightly in the overall cohort from 9.3% to 8.9% (p < 0.001). CONCLUSIONS: More than half of all elderly patients with a CICU stay across the U.S. now have primary non-cardiac diagnoses at discharge. These patients receive different types of care and have worse outcomes than patients with primary cardiac diagnoses. Our work has important implications for the development of appropriate training and staffing models for the future critical care workforce.